Study on catalyst based on CuO modified with Boron applied for selective oxidation of propylene to acrolein (Vietnam Journal of Catalysis and Adsorption, 2018)
This work studied on catalysts based on CuO modified with Boron for the selective oxidation of propylene to acrolein. These catalysts were prepared by precipitation with the addition of Boron from 4- 7 wt.%. XRD, BET techniques were applied to characterize the catalyst. The catalytic activity tests were carried out on micro-line reactor system connected with GC online with detector TCD. It was found that the catalyst CuO - 7% Boron was the best because of the highest rate of acrolein formation but the least rate of propylene consumption.